2010
DOI: 10.1053/j.gastro.2010.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Albinterferon Alfa-2b Was Not Inferior to Pegylated Interferon-α in a Randomized Trial of Patients With Chronic Hepatitis C Virus Genotype 2 or 3

Abstract: BACKGROUND & AIMS A phase 3 active-controlled study was conducted to assess the efficacy/safety of albinterferon alfa-2b (albIFN), a novel, long-acting, genetic fusion polypeptide of recombinant human albumin and interferon alfa-2b, in patients with chronic hepatitis C virus (HCV) genotype 2/3. METHODS In all, 933 patients were randomized to open-label subcutaneous treatment with pegylated interferon-alfa-2a (Peg-IFNalfa-2a) 180 μg/wk, or albIFN 900 or 1200 μg every 2 weeks for 24 weeks, each administered wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 31 publications
1
47
0
Order By: Relevance
“…The efficacy of alb-IFN was evaluated in clinical phase IIb studies with IFN-naive patients chronically infected with HCV, in which it was administered every 2 or 4 weeks (Zeuzem et al, 2008). The clinical studies showed that alb-IFN had similar anti-viral effects to pegIFN-a (Nelson et al, 2010;Zeuzem et al, 2010). However, in phase III studies, a higher incidence of serious pulmonary adverse events was observed in alb-IFN-treated patients, which resulted in the cessation of further development by Novartis and Human Genome Sciences in 2010.…”
Section: New Ifnsmentioning
confidence: 99%
“…The efficacy of alb-IFN was evaluated in clinical phase IIb studies with IFN-naive patients chronically infected with HCV, in which it was administered every 2 or 4 weeks (Zeuzem et al, 2008). The clinical studies showed that alb-IFN had similar anti-viral effects to pegIFN-a (Nelson et al, 2010;Zeuzem et al, 2010). However, in phase III studies, a higher incidence of serious pulmonary adverse events was observed in alb-IFN-treated patients, which resulted in the cessation of further development by Novartis and Human Genome Sciences in 2010.…”
Section: New Ifnsmentioning
confidence: 99%
“…Hence Peg-IFN-2a (Pegasys; Hoffmann-La-Roche) and Peg-IFN-2b (PegIntron; 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 10 Schering Plough), which consist respectively of a single (40 kDa) or several (12 kDa) polyethylene-glycol (Peg) chain(s) added to IFN backbone are currently used to treat CHB patients (Foster, 2010). Other modification included the addition of human albumin moiety to IFN backbone to generate a long half-life fusion protein (albinterferon), which was evaluated in stage III clinical trial in the context of HCV infections and showed no superiority to Peg-IFN (Nelson et al, 2010;Subramanian et al, 2007;Zeuzem et al, 2010). Moreover, in the context of HBV infection, albinterferon has shown higher rates of certain adverse effect as compared to Peg-IFN-, thus likely limiting its further development (Colvin et al, 2015).…”
Section: Modes Of Action Of Ifn-mentioning
confidence: 97%
“…Rates of each IITD subtype were not different by treatment arm (v 2 = 7.1, p = 0.3). This was expected because randomization was effective and the originally published safety analysis found that the treatment arm did not impact rates of thyroid disease by several different definitions (29). Thus, all further investigations were collapsed across treatment arm.…”
Section: Multivariate Logistic Regressionmentioning
confidence: 98%
“…Details of the original clinical trial design have been previously described (29). In brief, otherwise healthy adults with liver biopsy-proven chronic hepatitis C genotype 2 or 3 infection without prior IFNa therapy were recruited between 2007 and 2008 at 136 sites in India, Asia/Pacific, North and South America, and Europe.…”
Section: Achieve Study Design and Patient Characteristicsmentioning
confidence: 99%